2018
DOI: 10.1177/1179597218781081
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of a Fluorescent Imaging System to Detect Amyloid-β Proteins: Phantom Study

Abstract: Alzheimer disease is the most common form of dementia, affecting more than 5 million people in the United States. During the progression of Alzheimer disease, a particular protein begins to accumulate in the brain and also in extensions of the brain, ie, the retina. This protein, amyloid-β (Aβ), exhibits fluorescent properties. The purpose of this research article is to explore the implications of designing a fluorescent imaging system able to detect Aβ proteins in the retina. We designed and implemented a flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As a result, the peak produced by a fast Fourier transform (FFT) of the photodetected signal is not narrow around the frequency component given by 2n/T, where T is the period of the input triangular signal and n is the number of slits in the metal plate. Our aim is to alter the shape of each ramp in the triangular signal, using an optimization algorithm [22,[28][29][30][31][32][33][34], until the photodetected signal presented maximum regularity in the succession of peaks corresponding to the beam being scanned over regularly placed empty spaces, to produce equidistant spikes, and narrow the FFT peak. The galvo-mirror is driven by a triangular signal of 5-volt peak-to-peak.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, the peak produced by a fast Fourier transform (FFT) of the photodetected signal is not narrow around the frequency component given by 2n/T, where T is the period of the input triangular signal and n is the number of slits in the metal plate. Our aim is to alter the shape of each ramp in the triangular signal, using an optimization algorithm [22,[28][29][30][31][32][33][34], until the photodetected signal presented maximum regularity in the succession of peaks corresponding to the beam being scanned over regularly placed empty spaces, to produce equidistant spikes, and narrow the FFT peak. The galvo-mirror is driven by a triangular signal of 5-volt peak-to-peak.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that Aβ levels in the retina were closely related to those in the brain and confirmed that the retina was also an area of high plaque deposition. Furthermore, in 2018, Tes et al [48] tested Cy5 and CRANAD-2 (a compound derived from curcumin) as fluorescent probes for observing the growth of plaques in the retina with a fluorescence imaging system. The result shows that CRANAD-2 is a better fluorescent probe for Aβ imaging.…”
Section: Conventional Fluorescence Microscopy Imagingmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay and optical dye (Thioavin T and Congo Red) binding are the other techniques used for the study of kinetics of Ab 1-42 brillation. 11,12 These techniques also have disadvantages such as non-specic binding, low stability and crossreactivity. 13 As a result, these techniques are susceptible to falsepositive results.…”
mentioning
confidence: 99%